PENERAPAN MODEL PEMBELAJARAN SELF DIRECTED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR DI MAN 1 KOTA MAKASSAR - Hanafia, Irfan Muh; Akil, M; Azhar, Muh; Surani; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement in students' learning motivation through the implementation of the Self-Directed Learning model in the Islamic Cultural History subject in class XI.9 at MAN 1 Makassar City. The study employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted over two cycles; each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects comprised 30 students (12 male and 18 female). Data collection techniques included observation, interviews, tests, and documentation. Research instruments consisted of observation sheets for teacher and student activities, interview guidelines, test questions, and documentation. Data analysis was conducted using descriptive quantitative methods, specifically calculating average scores and the percentage of learning mastery. The results indicate that the implementation of the Self-Directed Learning model successfully increased student learning motivation in each cycle. In the pre-cycle stage, the average score was 61.43, with a learning mastery rate of 23.33% (7 students). Following the implementation of the Self-Directed Learning model in Cycle I, the average score rose to 75.43, with a learning mastery rate of 53.33% (16 students). Subsequently, Cycle II showed a more significant improvement, with the average score reaching 90.16 and the learning mastery rate hitting 93.33% (28 students); this surpassed the established success indicator, which required at least 80% of students to achieve a score of ≥75. Observation results also showed an increase in teacher activity from an average score of 3.33 (good) to 3.83 (very good), while student activity increased from 3.16 (good) to 3.91 (very good). Thus, it can be concluded that the implementation of the Self-Directed Learning model is effective in enhancing student learning motivation in the Islamic Cultural History subject in class XI.9 at MAN 1 Makassar City.